Evaluation of Ice Nucleation Activity in Zygomycetous Fungi: First Report of Ice Nucleation Active Linnemannia amoeboidea Isolated from Soil in Korea - Jin-Sil Choi; Seong-Keun Lim; Gwang-Jae Lim; Diane Avalos-Ruiz; Seung-Yeol Lee; HeeYoung Jung (한국균학회지)
Twenty-two strains of zygomycetous fungi were isolated from soil and selected based on their cultural characteristics. The strains were identified through similarity searches and a phylogenetic analysis of their internal transcribed spacer regions and 28S rDNA large subunit sequences. Cultural and morphological characteristics, including colony color and the sizes of sporangia, sporangiospores, and chlamydospores, were used to confirm the identity of KNUF-GWL1 as Linnemannia amoeboidea, a species not previously reported in Korea. Additionally, the twenty-two strains were evaluated for ice nucleation activity (INA) using a tube freezing test at −5℃. Among the isolated strains, five exhibited INA: KNUF-GWL1, KNUF-CNM1, KNUF-GBM2, KNUF-GBM3, and KNUF-GBM4. To assess the optimum growth temperature and the effect of growth temperature on the INA of INA-positive fungi, strains L. amoeboidea KNUF-GWL1 and Mortierella alpina KNUF-GBM4 were tested. Both strains exhibited their most vigorous growth at 25℃, with the number of ice nuclei increasing at lower incubation temperatures. To our knowledge, this study represents the first evaluation of INA in zygomycetous fungi isolated from soil and the first report of INA in L. amoeboidea.